2022
DOI: 10.1021/acsapm.1c01917
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Morphology in Epoxy/Thermoplastic Systems

Abstract: Thermosets are frequently toughened by a high-T g thermoplastic (TP). Blend morphologies obtained by curing induced phase separation with scales of a few hundreds of nanometers are relevant for high-performance applications, but no quantitative description for obtaining these morphologies exists yet. We propose such a quantitative approach for predicting and controlling the final morphology. The key is the degree of curing and the corresponding T g of the blend and both phases when phase separation takes place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Epoxy resins, an important class of thermosetting polymers, are widely used as adhesives and composite materials in a variety of manufacturing industries ranging from aerospace and automotive engineering to microelectronics, thanks to their excellent mechanical strength, thermal stability, and chemical resistance. Epoxy resins, generally obtained via the curing reaction of epoxy and hardener compounds, are amorphous and highly cross-linked networks with a glass transition temperature ( T g ) well above room temperature. , Thus, under ambient conditions, they are relatively brittle materials with a poor resistance to crack initiation and propagation . Over the past few decades, many attempts have been devoted to improving the fracture performance of epoxy materials by adding a second micro/nanophase of dispersed fillers into reaction mixtures prior to the network formation. Various types of fillers ranging from soft rubbers to hard inorganic particles have been proven to substantially increase the fracture toughness of epoxy resins, although their effects on other thermomechanical properties can vary. A comprehensive comparison of the effect of different filler types on the toughness and thermomechanical properties of epoxy resins has been reported by Kinloch and co-workers. For example, they found that the addition of approximately 10% by mass of silica nanoparticles to an epoxy matrix can simultaneously increase the fracture energy by ∼250% and elastic modulus by ∼15%, while the sample T g remains almost unchanged. They also observed a similar magnitude in the fracture energy increase for this epoxy resin when filled with approximately 9% by mass of rubber particles, but the epoxy modulus and T g are decreased by ∼20% and ∼15 K, respectively. , Studies from other research groups have also evidenced such a positive effect of silica nanoparticles on multiple physical properties for different epoxy systems. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins, an important class of thermosetting polymers, are widely used as adhesives and composite materials in a variety of manufacturing industries ranging from aerospace and automotive engineering to microelectronics, thanks to their excellent mechanical strength, thermal stability, and chemical resistance. Epoxy resins, generally obtained via the curing reaction of epoxy and hardener compounds, are amorphous and highly cross-linked networks with a glass transition temperature ( T g ) well above room temperature. , Thus, under ambient conditions, they are relatively brittle materials with a poor resistance to crack initiation and propagation . Over the past few decades, many attempts have been devoted to improving the fracture performance of epoxy materials by adding a second micro/nanophase of dispersed fillers into reaction mixtures prior to the network formation. Various types of fillers ranging from soft rubbers to hard inorganic particles have been proven to substantially increase the fracture toughness of epoxy resins, although their effects on other thermomechanical properties can vary. A comprehensive comparison of the effect of different filler types on the toughness and thermomechanical properties of epoxy resins has been reported by Kinloch and co-workers. For example, they found that the addition of approximately 10% by mass of silica nanoparticles to an epoxy matrix can simultaneously increase the fracture energy by ∼250% and elastic modulus by ∼15%, while the sample T g remains almost unchanged. They also observed a similar magnitude in the fracture energy increase for this epoxy resin when filled with approximately 9% by mass of rubber particles, but the epoxy modulus and T g are decreased by ∼20% and ∼15 K, respectively. , Studies from other research groups have also evidenced such a positive effect of silica nanoparticles on multiple physical properties for different epoxy systems. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…They found that the periodic distances of PEI phases are smaller with low MW PEI, which may be due to the tendency to disentangle easily. Moreover, the differences in phase morphologies may not only be attributed to the MW effect directly but also depend on the number of ‐NH 2 functional groups at rPEI chain ends 66,67 . Since the number of ‐NH 2 end groups in HrPEI would be lower than that of LrPEI at the same rPEI loading, the presence of reactive end groups may favor the miscibility of the rPEI with the epoxy precursors and therefore delay the phase separation 64,68 .…”
Section: Resultsmentioning
confidence: 99%
“…One can blend thermoplastics with thermoset resins and curing agents and then use postcuring reactions to achieve thermoplastic-thermoset blends with unique phase separation. [3,4] But such solution blending is very strict with pre-and postprocessing conditions. To eliminate the effect of interfacial defects, a convergence of chemistry and physics is usually required to strengthen the interaction of ingredients.…”
Section: Introductionmentioning
confidence: 99%